Evaluation of pupillary functions in adult vitamin D deficiency patients - Zeki baysal; Ömer Özer; Levent Doğan; Ercan Sezgın; Emin Serbülent Güçlü; Pınar Eröz (BMC Ophthalmology)
Abstract Purpose To evaluate the pupillary dynamics in patients with serum vitamin D (25(OH)-D) levels below normal and compared with healthy controls. Methods This study included 132 patients and 76 healthy controls. Serum 25(OH)-D concentrations within the range of 10 to 30 ng/mL were classified as vitamin D insufficiency (VDI, Group 1), while those at or below 10 ng/mL were categorized as vitamin D deficiency (VDD, Group 2). The static phase of pupillometry, including scotopic, mesopic, and photopic pupil diameters, was evaluated. Additionally, in the dynamic phase of pupillometric evaluation, pupil dilation velocity (mm/sec) was calculated. These values were compared between patient and control groups. Results In static pupil diameters, only photopic pupil diameters were significantly different between Groups 1 and 2 compared to the control group (p = 0.012 and p = 0.008, respectively). In dynamic measurements, the pupil diameter values showed a statistically significant difference between the patient and control groups (p = 0.003). In intragroup comparison, the mean pupil diameter was 3.42 ± 0.81 mm in group 1 and 3.94 ± 0.96 mm in group 2 (p = 0.029). Mean pupil dilation velocity was significantly slower in the patient group (p < 0.001). In intragroup comparison, the mean pupil dilation velocity was 0.162 ± 0.049 mm/sec in group 1 and 0.088 ± 0.032 mm/sec in group 2 (p < 0.001). Conclusion We demonstrated that VDD alters pupillary functions with objective measurements. Our study may shed light on the role of vitamin D in multisystemic diseases since it is expressed in many tissues and has multiple functions. Multicenter studies with a large number of participants are needed in the future.